Predominance of Type 1 Innate Lymphoid Cells in the Rectal Mucosa of Patients With Non‐Celiac Wheat Sensitivity: Reversal After a Wheat‐Free Diet. Issue 7 (July 2016) - Di Liberto, Diana; Mansueto, Pasquale; D'Alcamo, Alberto; Pizzo, Marianna Lo; Presti, Elena Lo; Geraci, Girolamo; Fayer, Francesca; Guggino, Giuliana; Iacono, Giuseppe; Dieli, Francesco; Carroccio, Antonio
Abstract : OBJECTIVES: : Non‐celiac wheat sensitivity (NCWS) is defined as a reaction to ingested wheat after exclusion of celiac disease and wheat allergy. As its pathogenesis is incompletely understood, we evaluated the inflammatory response in the rectal mucosa of patients with well‐defined NCWS. METHODS: : The prospective study included 22 patients with irritable bowel syndrome (IBS)‐like clinical presentation, diagnosed with NCWS by double‐blind placebo‐controlled challenge. Eight IBS patients not improving on wheat‐free diet were used as controls. Two weeks after oral challenge was performed with 80 grams of wheat daily, cells were isolated from rectal biopsies and thoroughly characterized by fluorescence‐activated cell sorting analysis for intracellular cytokines and surface markers. RESULTS: : Rectal biopsies from wheat‐challenged NCWS patients showed that a significant mucosal CD45 + infiltrate consisted of CD3 + and CD3 − lymphocytes, with the latter spontaneously producing more interferon (IFN)‐γ than IBS controls. About 30% of IFN‐γ‐producing CD45 + cells were T‐bet +, CD56 −, NKP44 −, and CD117 −, defining them as a type‐1 innate lymphoid cells (ILC1). IFN‐γ‐producing ILC1 cells significantly decreased in 10 patients analyzed 2 weeks after they resumed a wheat‐free diet. CONCLUSIONS: : These data indicate that, in patients with active NCWS, IFN‐γ‐producing ILC1 cells infiltrate rectal mucosa and support a role for this innate lymphoid cell population in the pathogenesis of NCWS.